أثر هيكل التمويل على ربحية السهم العادي ومعدلات نمو الوحدات الاقتصادية - قابوسة, علي (جامعة الوادي - University of Eloued, 2008)
تعمل الوحدات الاقتصادية على تحقيق هيكل التمويل الأمثل الذي يحقق أكبر ربح اوعائد للمالكين والذي يؤدي إلى تعظيم القيمة السوقية للأسهم التي تصدرها الوحدة الاقتصادية إلى أقصى حد ممكن . إن طريقة التمويل المختارة يجب أن تؤدي إلى تخفيض كلفة التمويل إلىأقصى حد ممكن (6) ، لأن طريقة التمويل تؤثرعلى ربحية المشروع وبتالي على ربحية أسهمه لذا فإنه من الأهمية أن يؤدي اختيار هيكل التمويل إلى تحقيق التوازن بين الأرباح والمخاطرة المرتبطة بهيكل التمويل ذاته ألا وهي المخاطرة التمويلية التي تتأثربمدى مسهامة كل من الديون وحقوق الملكية في تكوين هيكل التمويل ، أي تأثرها بالرافعة التمويلية للوحدة الاقتصادية التي هي علاقة بين إجمالي الخصوم إجمالي الأصول والتي تكون مرغوبة عندما يكون العائد المتحقق علي الأصول أكبر من تكلفة الديون . The economic units work to achieve the optimal financing structure that achieves the largest profit to the owners, which maximizes the market value of the shares issued by the economic unit. The financing method chosen should reduce the cost of financing to the maximum extent possible, 6 because the method of financing affects the profitability of the project and depends on the profitability of its shares. Therefore, it is important that the choice of financing structure balances the profits and risk associated with the financing structure itself Which is affected by the leverage of the economic unit that is the relationship between total liabilities and total assets that are desirable when the return on assets is greater than the cost of the debt.
مقال
Keywords: هيكل التمويل، مصادير التمويل، عائد السهم; Financing structure, financing volumes, earnings per share